Morphological-anatomical characterization and identification of Tomentella ectomycorrhizas. - Jakucs, Erzsébet; Eros-Honti, Zsolt (Mycorrhiza, 2008)
Over the last two decades, much information has been gathered on the ectomycorrhizal fungus community composition of plant associations of boreal, temperate, and tropical regions. Worldwide, Tomentella ectomycorrhizas (ECM) are often common and dominant in the mycorrhizosphere of coniferous and deciduous forests. They are present under different environmental conditions and associate with diverse plant hosts. Tomentella sporocarps, however, are rarely found aboveground, so Tomentella species are often missing from fungus community studies based on fruit-body presence. Tomentella is a resupinate genus of Thelephoraceae (Basidiomycota) forming black-brown, brown, yellow, or ochre ECM on the roots of gymnosperm and angiosperm trees, distinguished by typical morphological-anatomical characteristics (clamped hyphae, angular mantle, surface network, special rhizomorphs and cystidia). In this paper, we review the taxonomic position and morphological-anatomical characteristics of Tomentella ECM. A short summary of the microscopic features used for distinguishing tomentelloids during morphotyping and identification is presented in order to support molecular and ecological studies of ectomycorrhizal fungus communities.
Keywords: Anatomy; ECM; ectomycorrhiza; identification; morphology; Tomentella